2012
DOI: 10.1097/nne.0b013e31825a875a
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Millennial Generation

Abstract: A particular challenge for nurse educators has always been to discover the most relevant ways to promote student learning. Each generation of students presents with unique circumstances. The predominant characteristics of the current generation of nursing students are presented in this article. Suggestions are given regarding strategies to strengthen and maintain the characteristics that will be beneficial to students when they become RNs, while at the same time modifying or diminishing those that will not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“… 12 It also promotes collaboration, a key trait identified with the current generation of students classified as “millenials”. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 It also promotes collaboration, a key trait identified with the current generation of students classified as “millenials”. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The unique characteristics of Millennial nursing students require nursing faculty to develop innovative teaching strategies. These students are often described as optimistic, assertive, creative, committed, multitasking, and cooperative team players (Johanson, 2012;Mangold, 2007), and they prefer entertainment, technology, experiential learning, and a focus on teamwork (McCurry & Martins, 2010). These students also are accustomed to immediate feedback and desire positive reinforcement (McCurry & Martins, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…These students also are accustomed to immediate feedback and desire positive reinforcement (McCurry & Martins, 2010). Experiential learning activities, such as simulation, promote reflection and development of reasoning skills in Millennial nursing students (Johanson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the lack of concentration, engagement, and socialization can impact the outcomes of learning. [7][8][9] By supporting learning activities that increase engagement, retention of information improves, along with improved outcomes for the learners. 3,7 Multisensory learning can integrate digital technology, use real-world examples, and help learners to fully take part in the experience.…”
mentioning
confidence: 99%
“…[7][8][9] By supporting learning activities that increase engagement, retention of information improves, along with improved outcomes for the learners. 3,7 Multisensory learning can integrate digital technology, use real-world examples, and help learners to fully take part in the experience. The use of digital technology can also be used to provide collaborative learning to fit the unique needs of the students and effectively meet learning outcomes.…”
mentioning
confidence: 99%